Cross-Chapter Box NATURAL | Nature-Based Solutions for Climate Change Mitigation and Adaptation - Adrian, Rita (2023)
Nature-based solutions provide adaptation and mitigation benefits for climate change as well as contributing to other sustainable development goals (high confidence). Effective nature-based climate change mitigation stems from inclusive decision-making and adaptive management pathways that deliver climate-resilient systems serving multiple sustainable development goals. Robust decision-making adjusts management pathways as systems are impacted by ongoing climate change. Poorly conceived and poorly designed nature-based mitigation efforts have the potential for multiple negative impacts, including competing for land and water with other sectors, reducing human well-being and failing to provide mitigation that is sustainable in the long term (high confidence).